The McDonaldization of Psychotherapy? (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
Are we seeing an increasingly commodified, process-driven and risk-averse approach to psychotherapy? Starting with an operational model pioneered by the global fast-food giant that has subsequently been adopted by major public institutions and professional bodies, this paper examines the evidence for McDonaldization terms of language, personal responsibility and policy – and the implications for client care.
Keywords: State therapy; language; McDonaldization; McRisk; Critical Psychotherapy